Estimation of logatom intelligibility with the STI method for Polish speech transmitted via communication channels - S. Brachmański (Archives of Acoustics)
An objective measure of the quality of speech communication channels was introduced and described by Steeneken-Houtgast. By calculating the Speech Transmission Index (STI), this method provides an estimate of logatom intelligibility for a variety of communication distortions. Using the logatom test for speech intelligibility, it was shown that the STI method is a valid method for the assessment of the quality of the speech transmitted over communications channels intended for use with the Polish language. New STI curves were generated for the Polish speech intelligibility. Key words: speech quality, speech intelligibility, logatom intelligibility, speech transmission index, STI.